Factors influencing the success of aerial rabies vaccination of foxes. Issue 1 (December 2017) - Henning, J.; Giorgi, E.; Soares Magalhães, R.; Tizzani, P.; Viviani, P.; Pejovic, N.; Hrapović, M.; Potzsch, C.
Abstract Sylvatic rabies has been eradicated from most of Central Europe, but cases still occur in the Balkans. Oral rabies vaccination of foxes is an effective method for controlling the disease. The aim of this study was to evaluate the success of aerial vaccination campaigns conducted in Montenegro by identifying ecological, environmental and climatic factors that influenced the prevalence of antibodies to the rabies vaccine. To monitor the bait uptake and the serological responses to vaccination, foxes were shot by hunters. Of 175 shot foxes, 142 foxes (81.1%) had consumed baits. Of these only a total of 81 (57.0%) tested positive for rabies vaccine antibodies, possibly, due to the delayed uptake of bait in which the rabies vaccine was already inactivated. We found that low vaccination responses were associated with high fox density and bait delivery in open areas. In high fox density habitat, bait uptake might be delayed as other food and prey options for foxes are abundant. Similarly, delayed bait uptake probably occurred in open areas as such areas are less frequently used by foxes. The findings of this study suggest that efficacy of oral rabies vaccination by aerial delivery is associated with landscape features.